A General Framework of Resource Allocation Optimization and Dynamic Scheduling - Shuang Chang; Manabu Ichikawa; Hiroshi Deguchi; Yasuhiro Kanatani (SICE Journal of Control, Measurement, and System Integration, 2017)
Resource allocation and scheduling under scarce resources and limited time are always critical and challenging tasks, not only because of the complex situation with diverse needs involved, but also of any unpredictable occurrence during the whole dynamic process. This work proposes an agent-based framework to integrate the resource allocation and scheduling under a set of limitations, which could respond to contingent changes as a dynamic system. We focus on the following research questions and formulate them as a constraint satisfaction problem: how many resources should be assigned and dispatched to which location, in which sequence and under what process scheduling with time, resource availability, and ability-matching limits. We first give the corresponding formal definition, and then combine real-coded genetic algorithm and dynamic scheduling of multi-functional resource assignment to tackle the above proposed research questions. In addition, we experiment the model with a small make-up case to suggest some preliminary scenarios. In future, this framework would be further applied to real life emergency situations with empirical data for training purposes and providing insight for relevant policy makers.